2017
DOI: 10.1371/journal.pone.0179605
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-34 inhibits hepatitis B virus replication in vitro and in vivo

Abstract: BackgroundThe hepatitis B virus (HBV) infection could activate the immune system and induce extensive inflammatory response. As the most important inflammatory factor, interleukins are critical for anti-viral immunity. Here we investigated whether interleukin-34 (IL-34) play a role in HBV infection.Methodology/Principal findingsIn this study, we first found that both serum IL-34 and IL-34 mRNA in PBMCs in chronic HBV patients was significantly decreased compared to the healthy controls. Furthermore, both IL-34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…IL‐34 is considered to be associated with HBV infection and HCC . However, the role and associated mechanisms of IL‐34 in HBV‐related HCC are not well clarified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IL‐34 is considered to be associated with HBV infection and HCC . However, the role and associated mechanisms of IL‐34 in HBV‐related HCC are not well clarified.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Importantly, recent studies show that IL-34 is involved in the HBV infection and associated with liver fibrosis. 14,15 Besides, the report from Zhou S et al shows that increased IL-34 is related to the poor survival and tumour recurrence in HCC patients, and modulates the invasion and metastasis of HCC cells via macrophages. 16 However, whether IL-34 contributes to the development of HBV-infected HCC is still unclear.…”
Section: Hepatitis B Virus (Hbv) Is One Of the Most Vital Aetiologicamentioning
confidence: 99%
See 1 more Smart Citation
“…Since IL‐34 is expressed at mRNA level in various tissues, this expression is expected to be changed under pathological conditions. Indeed, several studies have confirmed the enhancement of IL‐34 expression at mRNA and protein levels in the context of various diseases including autoimmune disorders, inflammation, infections, metabolic diseases, neurological disorders, and cancer . At the cellular level, IL‐34‐producing cells include synovial fibroblasts, immune cells, epithelial cells, endothelial cells, adipocytes, and cancer cells.…”
Section: Il‐34 Biologymentioning
confidence: 95%
“…An overexpression of IL-34 has been reported in some severe diseases associated with chronic inflammation, such as viral infections [37,77], inflammatory bowel diseases [78], rheumatoid arthritis [76,79], systemic lupus erythematosus [80], and Sjogren's syndrome [81]. In contrast, one study has reported a decrease in IL-34 expression in patients chronically infected by hepatitis B virus [82].…”
Section: Il-34 In Inflammatory Disordersmentioning
confidence: 99%